Bean Research Methods Training Course, Bunda College of Agriculture, Malawi: report - Mutimba, J. (National Bean Programme, 1990)
General information is given of the bean research methods training course held in Malawi from 20-31 Aug. 1990: background, participants, trainers, objectives, participants expectations, official opening, subject content, field trip, progress evaluation, participants' evaluation of the course, course expenses, and closing ceremony. (CIAT)